PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP PRODUK KOSMETIK YANG MENGANDUNG BAHAN BERBAHAYA - Vini Alvionita (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACT Trading in a free era is now a lot of cosmetics on the market and through social media with various types of brands. A woman's desire to always look beautiful is widely utilized by irresponsible businesses by producing or trading cosmetics that do not meet the requirements or that contain harmf ingredients to distributed to the public. Most wome are very interested in buying kosemetik products at low prices and the results are quickly visible. Many loss are caused by the circulation of cosmetic products face whitening but this danger is not realized by women. The government invited Law No. 8 of 1999 on Consumer Protection to be fully protected and protected consumer rights. This paper aims to know the legal protection for consumers against products containing hazardous materials and to know the legal sanctions against kosetic businesses containing materials containing hazardous materials. This research method uses NormativeEmpirical. This method of empirical normative law research is basically a merger between normative legal approaches with the addition of various empirical elements. Based on the results of the study explained that legal protection for consumers against cosmetic products containing harmful ingredients is still found in the city of Samarinda that are still circulating and sold by manufacturers and businesses that are not responsible as stipulated in Law No. 8 of 1999 on Consumer Protection. Producers and businesses that do not meet the requirements in producing the sale of an item will be subject to criminal sanctions Article 169 for a maximum of 10 (ten) years and a maximum fine of Rp 1,000,000,000.00 (one billion rupiahs) and Article 19 7 with the threat of until 15 (fifteen) years and a maximum fine of Rp 1,500,000,000.00 (one billion five hundred million rupiahs) which has been regulated in Law No. 36 of 2009 concerning Health.Keywords: Consumer Protection, Dangerous Cosmetics